2002
DOI: 10.1161/01.str.0000027638.19392.7e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Misery Perfusion With Split-Dose 123 I-Iodoamphetamine Single-Photon Emission Computed Tomography in Patients With Carotid Occlusive Diseases

Abstract: Background and Purpose-Patients with carotid occlusive disease and stage 2 cerebral hemodynamic failure, characterized by an increased oxygen extraction fraction (OEF) as measured by positron emission tomography (PET) and otherwise known as misery perfusion, have a high risk of cerebral ischemia and subsequent stroke. In clinical practice, the detection of patients with misery perfusion through the use of widely available, noninvasive, and cost-effective modalities such as single-photon emission computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Many earlier studies have evaluated the relationships between OEF and CVR (8,9,13,14). Most of these studies have concluded that there is a significant correlation between OEF and CVR to acetazolamide (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many earlier studies have evaluated the relationships between OEF and CVR (8,9,13,14). Most of these studies have concluded that there is a significant correlation between OEF and CVR to acetazolamide (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have concluded that there is a significant correlation between OEF and CVR to acetazolamide (13,14). However, in these studies, the number of patients included was low.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their clinical conditions, the patients underwent [ 16 The details of SPECT procedure were reported previously. 16 Based on the neuroradiological reports, the degree of CBF impairment in the affected ICA or MCA region was categorized into 3 classes: no significant CBF reduction at rest (class A), CBF reduction at rest but with preserved vasoreactivity to acetazolamide (class B), and reduction at rest with impaired vasoreactivity (Ͻ23% increase) to acetazolamide as determined by a split-dose method (class C).…”
Section: Cbf Study With Spectmentioning
confidence: 99%
“…The CVR is often measured by SPECT or xenon-CT before and after administering a vasodilator, such as CO 2 or acetazolamide, 6 and the combination of the lower CVR and lower CBF is a reliable index for accurately detecting the existence of increased OEF, which is known as misery perfusion. 7 Recently, the advancement of MR imaging modalities has enabled to investigators to evaluate small venous structures and iron in the brain. In particular, SWI has been accepted as a method available to evaluate deep venous flow in acute or chronic ischemia and to demonstrate increased oxygen extraction in focal cerebral ischemia.…”
mentioning
confidence: 99%